,,Głos Wielkopolanek – tygodnik społeczno-narodowy dla kobiet wszystkich stanów’’ (1908-1924) – stan badań i możliwości źródłowe - Cieślik, Agata (Studia Edukacyjne, 2025)
The author takes up the topic of the state of research around the Głos Wielkopolanek magazine. Citing successive ways of characterizing it so far and examples of the use of the contents, she demonstrates the numerous research opportunities offered by the periodical.